Ecotoxicity and Hemolytic Activity of Fluorinated Ionic Liquids - Vieira, Nicole S. M. (2022)
The task-specific design of ionic liquids (ILs) has emerged in several industrial and pharmaceutical applications. The family of ILs with fluorine tags equal to or longer than four carbon atoms, the fluorinated ionic liquids (FILs), combine the best properties of ILs with the ones of perfluorinated compounds, and are being designed for several specific purposes. In the pharmaceutical field, there is an urgency to search for novel antibacterial agents to overcome problems associated to antimicrobial resistances. Then, the main purpose of this work is to evaluate the environmental impact and the ability of FILs to be used as antibacterial agents against Pseudomonas stutzeri bacteria. Beyond its rare pathogenicity, these bacteria are also used as a bioremediation agent to treat several contamination sites. Then, it is important to determine which FILs have antibacterial properties, and which do not impact the bacterial growth. The biocompatibility of FILs was also evaluated through their hemolytic activity and represent a step forward the application of FILs in pharmaceutical applications. The results proved that high concentrations of FILs can have a reduced ecotoxicity and a high biocompatibility. [C8C1Im][CF3SO3] was identified as the most promising compound to be used as an antibacterial agent since it prevents the growth of bacteria at concentrations compatible with the red blood cells’ viability.